Modulating the pharmacokinetic profile of Actinium-225-labeled macropa-derived radioconjugates by dual targeting of PSMA and albumin - Reissig, Falco; Zarschler, Kristof; Novy, Zbynek; Petrik, Milos; Bendova, Katerina; Kurfurstova, Daniela; Bouchal, Jan; Ludik, Marie-Charlotte; Brandt, Florian; Kopka, Klaus; Khoylou, Marta; Pietzsch, Hans-Jürgen; et al. (Theranostics, 2022)
Rationale: Small 225Ac-labeled prostate-specific membrane antigen (PSMA)-targeted radioconjugates have been described for targeted alpha therapy of metastatic castration-resistant prostate cancer. Transient binding to serum albumin as a highly abundant, inherent transport protein represents a commonly applied strategy to modulate the tissue distribution profile of such low-molecular-weight radiotherapeutics and to enhance radioactivity uptake into tumor lesions with the ultimate objective of improved therapeutic outcome. Methods: Two ligands mcp-M-alb-PSMA and mcp-D-alb-PSMA were synthesized by combining a macropa-derived chelator with either one or two lysine-ureido-glutamate-based PSMA- and 4-(p-iodophenyl)butyrate albumin-binding entities using multistep peptide-coupling chemistry. Both compounds were labeled with [225Ac]Ac3+ under mild conditions and their reversible binding to serum albumin was analyzed by an ultrafiltration assay as well as microscale thermophoresis measurements. Saturation binding studies and clonogenic survival assays using PSMA-expressing LNCaP cells were performed to evaluate PSMA-mediated cell binding and to assess the cytotoxic potency of the novel radioconjugates [225Ac]Ac-mcp-M-alb-PSMA and [225Ac]Ac-mcp-D-alb-PSMA, respectively. Biodistributions of both 225Ac-radioconjugates were investigated using LNCaP tumor-bearing SCID mice. Histological examinations of selected organs were performed to analyze the occurrence of necrosis using H&E staining, DNA damage via γH2AX staining and proliferation via Ki67 expression in the tissue samples. Results: Enhanced binding to serum components in general and to human serum albumin in particular was revealed for [225Ac]Ac-mcp-M-alb-PSMA and [225Ac]Ac-mcp-D-alb-PSMA, respectively. Moreover, the novel derivatives are highly potent PSMA ligands as their KD values in the nanomolar range (23.38 and 11.56 nM) are comparable to the reference radioconjugates [225Ac]Ac-mcp-M-PSMA (30.83 nM) and [225Ac]Ac-mcp-D-PSMA (10.20 nM) without albumin binders. The clonogenic activity of LNCaP cells after treatment with the 225Ac-labeled ligands was affected in a dose- and time-dependent manner, whereas the bivalent radioconjugate [225Ac]Ac-mcp-D-alb-PSMA has a stronger impact on the clonogenic cell survival than its monovalent counterpart [225Ac]Ac-mcp-M-alb-PSMA. Biodistribution studies performed in LNCaP tumor xenografts showed prolonged blood circulation times for both albumin-binding radioconjugates and a substantially increased tumor uptake (46.04 ± 7.77 %ID/g for [225Ac]Ac-mcp-M-alb-PSMA at 128 h p.i. and 153.48 ± 37.76 %ID/g at 168 h p.i. for [225Ac]Ac-mcp-D-alb-PSMA) with favorable tumor-to-background ratios. Consequently, a clear histological indication of DNA damage was discovered in the tumor tissues, whereas DNA double-strand break formation in kidney and liver sections was less pronounced. Conclusion: The modification of the PSMA-based 225Ac-radioconjugates with one or two albumin-binding entities resulted in an improved radiopharmacological behavior including a greatly enhanced tumor accumulation combined with a rather low uptake in most non-targeted organs combined with a high excretion via the kidneys.
Keywords: Tissue Distribution; nádorové buněčné linie; ligandy; Radiopharmaceuticals; radiofarmaka; sérový albumin; Mice, SCID; mužské pohlaví; PSMA; Albumin Binder; Mice; Actinium; Cell Line, Tumor; Serum Albumin; Ligands; Macropa; zvířata; tkáňová distribuce; Humans; Targeted Alpha Therapy; myši; myši SCID; lidé; Male; Animals